Preparation method and application of multi-layer carbon-coated silicon-carbon composite material
The multi-layer carbon-covered silicon-carbon composite material prepared by multi-layer coating and wire drawing technology solves the problems of poor cycle life and low Coulomb efficiency in lithium-ion batteries, and achieves high electrochemical performance and cycle stability.
Patent Information
- Application Number
- CN202411180983.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-08-27
AI Technical Summary
The existing silicon-carbon composite materials have problems such as poor cycle life and low efficiency of first charge and discharge in lithium-ion batteries. In addition, single-carbon layer silicon/carbon composite materials are prone to cracks caused by repeated deformation during long-term use, resulting in electrode failure.
Multi-layer coating and wire drawing technology are used to prepare multi-layer carbon-covered silicon-carbon composite materials. The nano-silicon powder is initially dispersed through carbon sources such as xylose and sucrose and surfactants, and a carbon fiber network is formed through asphalt wire drawing. Combined with chemical vapor deposition, amorphous carbon layer is coated to form a fine-structured multi-layer carbon-covered silicon-carbon composite material.
It effectively improves the electrochemical performance of the battery, improves the electrochemical activity, has high first-time Coulomb efficiency, excellent rate performance and cycle stability, and reduces the impact of silicon agglomeration and volume expansion on the electrode.
Smart Images

Figure CN118712370B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials and relates to a preparation method and application of a multi-layer carbon-coated silicon-carbon composite material. Background Art
[0002] In recent years, silicon-based anode materials have been widely used because of their significantly higher capacity than commercial graphite (theoretical capacity of 372 mAh g -1 ) with a high specific capacity (3579 mAh g -1 ), low voltage platform (≈0.4 V vs Li / Li + ), environmental friendliness and abundant reserves, and are suitable for meeting the needs of the next generation of high energy density lithium-ion batteries (LIBs) in new energy vehicle power battery applications. However, in practical applications, silicon is a semiconductor material, and its poor conductivity and volume expansion caused by the crystalline state of silicon (>300%) limit its application in lithium-ion batteries. In order to solve these problems, improvements are usually made in terms of material selection and structural design, such as alloying, composite, porous, nano-scale and other methods.
[0003] So far, people have developed various architectures of silicon-based composite materials, especially silicon-carbon composite materials. At present, carbon coating methods (such as chemical vapor deposition, liquid phase coating, ball milling, spray drying, etc.) are mostly used to form an amorphous carbon layer on the silicon surface. When the carbon layer is introduced, it not only acts as a protective layer to buffer the stress and volume change caused by silicon expansion, but also provides a high conductive layer to increase the conductivity of the material. However, there are also defects such as uneven distribution of silicon powder particles, incomplete carbon coating, and poor mechanical strength, which makes the single carbon layer silicon / carbon composite material still break and cracks formed by repeated deformation in the long-term silicon-lithium alloying / de-alloying reaction, resulting in electrode failure. Therefore, the development and optimization of multifunctional double shells and other composite structures (sandwich, passion fruit, etc.) have attracted widespread attention. In addition, the large-scale industrialization of silicon-carbon composite materials is also a research hotspot of silicon-carbon composite materials. At present, lithium-ion batteries generally have problems such as poor cycle life and low first charge and discharge coulomb efficiency, and the electrochemical performance indicators of silicon-carbon composite materials need to be further improved. Summary of the invention
[0004] In order to solve the above problems existing in the prior art, the purpose of the present invention is to provide a method for preparing a multi-layer carbon-coated silicon-carbon composite material and its application. A silicon-carbon composite material with a fine structure is prepared by multi-layer coating and wire drawing technology, which is applied to lithium-ion batteries to effectively improve the electrochemical performance of the battery.
[0005] One object of the present invention is achieved by the following technical solutions:
[0006] A method for preparing a multi-layer carbon-coated silicon-carbon composite material comprises the following steps:
[0007] S1, adding nano silicon powder and surfactant to an aqueous solution containing a first carbon source, stirring evenly, and drying to obtain a silicon-carbon precursor; in an inert atmosphere, subjecting the silicon-carbon precursor to a first high-temperature carbonization, ball milling, and sieving to obtain a Si@C composite material;
[0008] S2, adding Si@C composite material to the softened second carbon source, stirring evenly, and drawing to obtain a fibrous silicon-carbon precursor; subjecting the fibrous silicon-carbon precursor to a second high-temperature carbonization under an inert atmosphere, ball milling, and sieving to obtain a Si@C / carbon fiber composite material;
[0009] S3. The Si@C / carbon fiber composite material is subjected to chemical vapor deposition in an inert atmosphere and a third carbon source atmosphere to obtain a multi-layer carbon-coated silicon-carbon composite material.
[0010] Preferably, the average particle size of the nano silicon powder is 1-100 nm, more preferably 10-80 nm. Nano silicon powder has high activity, but is prone to agglomeration during the preparation process. The multi-layer carbon coating preparation method of the present invention is conducive to uniformly dispersing the nano silicon powder and solving the problem of its easy agglomeration.
[0011] Preferably, the surfactant is one or more of hexadecyltrimethylammonium bromide, dodecyltrimethylammonium bromide, polyvinylpyrrolidone, sodium carboxymethylcellulose, and sodium polyacrylate. The surfactant is added to slow down the aggregation of nano-silicon.
[0012] Preferably, the first carbon source is one or more of xylose and sucrose; more preferably, the first carbon source is a mixture of xylose and sucrose in a mass ratio of 1 to 2: 1. Xylose and sucrose contain rings in their molecular structures, which form a rigid carbon layer after carbonization, providing a certain mechanical strength and limiting the volume change of Si; and xylose and sucrose have good affinity with silicon, which can alleviate the agglomeration of silicon.
[0013] Preferably, in the aqueous solution containing the first carbon source, the concentration of the first carbon source is 10-800 g / L, more preferably 50-500 g / L. After adding the surfactant, the concentration of the surfactant is preferably 0.1-100 g / L, more preferably 1-50 g / L. The mass ratio of the nano silicon powder to the first carbon source is preferably 0.5-5:1, more preferably 1-2:1.
[0014] Preferably, the stirring temperature of step S1 is 20-80°C, the stirring rate is 200-1500 rpm, and the stirring time is 6-40 hours. More preferably, in step S1, the first stirring is performed first, and then the second stirring is performed, the temperature of the first stirring is 20-45°C, the stirring rate is 600-1500 rpm, and the stirring time is 10-60 minutes; the temperature of the second stirring is 45-80°C, the stirring rate is 200-600 rpm, and the stirring time is 2-30 hours.
[0015] Preferably, the drying temperature in step S1 is 70-120° C., and the drying time is 5-30 hours.
[0016] Preferably, the inert atmosphere is one or both of an argon atmosphere and a nitrogen atmosphere.
[0017] Preferably, the conditions of the first high temperature carbonization and the second high temperature carbonization include: a heating rate of 0.5-10°C / min, a carbonization temperature of 700-1000°C, and a carbonization time of 0.5-5h. The conditions of the first high temperature carbonization and the second high temperature carbonization can be the same or different.
[0018] Preferably, the ball milling conditions in steps S1 and S2 include: a ball milling speed of 150-500 r / min, and a ball milling time of 0.5-2 h. The ball milling conditions in steps S1 and S2 may be the same or different.
[0019] Preferably, the mesh sizes of the sieves in steps S1 and S2 are 100 to 800 meshes respectively. The mesh sizes of the sieves in steps S1 and S2 may be the same or different.
[0020] Preferably, the second carbon source is heated and softened at a high temperature in a muffle furnace, and the softening temperature is 380-500°C.
[0021] Preferably, the second carbon source is asphalt or polyacrylonitrile. Further preferably, the second carbon source is asphalt, and the carbon fibers formed by asphalt have better toughness and conductivity.
[0022] Preferably, in step S2, the mass ratio of the second carbon source to the Si@C composite material is 0.1-2:1.
[0023] Preferably, the stirring time of step S2 is 0.5-3 h, and the stirring speed is 100-800 rpm.
[0024] Preferably, during the wire drawing process of step S2, the heating temperature is 300-400°C, and the diameter of the fibrous silicon-carbon precursor obtained by wire drawing is 10 nm-2 μm.
[0025] The wire drawing of the present invention can be carried out on an extrusion wire drawing machine or a cyclone wire drawing device. When using an extrusion wire drawing machine, the applied pressure is 1 to 10 tons, the heating temperature is 300 to 400°C, the pore size is 200 to 300 μm, and the drawing height is 1 to 2 m; when using a cyclone wire drawing device, the rotation speed is 5000 to 10000 rpm and the heating temperature is 300 to 400°C.
[0026] Preferably, in step S3, the third carbon source is one or more of acetylene, methane, ethanol, and ethylene. The gas flow rate of the third carbon source atmosphere is 50-600 sccm, and the gas flow rate of the inert atmosphere is 400-800 sccm. The reaction gas pressure is 300-700 Pa.
[0027] Preferably, the chemical vapor deposition conditions in step S3 include: a heating rate of 1-10° C. / min, a temperature of 800-1000° C., and a time of 0.5-5 h.
[0028] The Si@C / carbon fiber composite material formed by drawing and carbonization has relatively large pores, which are sealed by a subsequent chemical vapor deposition carbon coating layer.
[0029] The second object of the present invention is achieved by the following technical solutions:
[0030] The preparation method mentioned above prepares a multi-layer carbon-coated silicon-carbon composite material.
[0031] The third object of the present invention is achieved by the following technical solutions:
[0032] The multi-layer carbon-coated silicon-carbon composite material is used in a lithium-ion battery, and the negative electrode sheet of the lithium-ion battery includes the multi-layer carbon-coated silicon-carbon composite material.
[0033] Preferably, the raw material including the multi-layer carbon-coated silicon-carbon composite material is mixed with a solvent to prepare a slurry, which is coated on a current collector and dried to obtain a negative electrode sheet.
[0034] Preferably, the raw material includes the multi-layer carbon-coated silicon-carbon composite material and a binder; the mass ratio of the multi-layer carbon-coated silicon-carbon composite material to the binder is (89~98):(2~11).
[0035] Preferably, the raw material includes the multi-layer carbon-coated silicon-carbon composite material, a conductive agent and a binder; the mass ratio of the multi-layer carbon-coated silicon-carbon composite material, the conductive agent and the binder is (87~97): (0.5~5): (2~10).
[0036] The conductive agent, binder and solvent are all commonly used substances in the preparation process of negative electrode sheets and are not particularly limited here.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] 1. The present invention adopts multi-layer coating and wire drawing technology to prepare a finely structured silicon-carbon composite material, which can effectively avoid the agglomeration of silicon, alleviate the volume expansion of silicon and the instability of SEI film. First, the agglomerated nano-silicon powder is preliminarily dispersed by carbon sources such as xylose and sucrose and surfactants, and the nano-silicon powder is uniformly coated with a layer of hard carbon. This rigid shell can provide a certain mechanical strength, limit the volume change of Si, keep the volume of the electrode constant, and improve safety. Secondly, the carbon fiber produced by asphalt wire drawing can form an effective electronic conductive interconnection network, which can further disperse the nano-silicon powder, so that silicon is evenly dispersed in the three-dimensional network of carbon fiber, increase the pore contact between active materials, facilitate the rapid diffusion of lithium ions, and reserve sufficient space for the volume expansion of silicon, and improve the ability of the surrounding environment to resist volume changes. Finally, the outer carbon layer supported by amorphous carbon coated by chemical vapor deposition not only makes the Si@C nanoparticles tightly adsorbed in the conductive carbon fiber network, but also regenerates the carbon coating layer on the surface of Si@C particles that is damaged by processes such as ball milling and screening, effectively improving the overall conductivity of the electrode.
[0039] 2. When the multi-layer carbon-coated silicon-carbon composite material prepared by the present invention is used as a negative electrode material for lithium-ion batteries, it can effectively improve the electrochemical activity and has a high first coulombic efficiency, excellent rate performance and cycle stability.
[0040] 3. By adjusting the amount of added carbon source (xylose, sucrose, asphalt, methane and acetylene), wire drawing process and CVD coating process and other parameters, the required silicon-carbon content ratio can be controlled, so as to design the expected charge and discharge specific capacity in the application of lithium-ion batteries to meet the actual industrial application needs.
[0041] 4. The coated carbon source used in the present invention comes from raw materials such as xylose, sucrose, and asphalt, which are inexpensive and easily available, can reduce the cost of commercial production and promote the large-scale production and application of silicon-carbon composite materials.
[0042] 5. The instruments and equipment used in the preparation process of the present invention can achieve mass production of more than one kilogram, laying the foundation for subsequent larger-scale commercial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 A schematic diagram of the structure of a multi-layer carbon-coated composite material provided by the present invention;
[0044] Figure 2 is a scanning electron microscope image of the multilayer carbon-coated composite material prepared in Example 1;
[0045] Figure 3 is an X-ray diffraction pattern of the multilayer carbon-coated composite material prepared in Example 1;
[0046] Figure 4 The first three charge-discharge curves of the multilayer carbon-coated composite material prepared in Example 1 as a lithium-ion negative electrode material;
[0047] Figure 5 It is a cycle curve diagram of the multilayer carbon-coated composite material prepared in Example 1 as a lithium ion negative electrode material. DETAILED DESCRIPTION
[0048] The technical scheme of the present invention is further described below by specific examples and accompanying drawings. It should be understood that the specific examples described herein are only used to help understand the present invention and are not intended for specific limitations of the present invention. The accompanying drawings used herein are only for better illustrating the disclosure of the present invention and do not have a limiting effect on the scope of protection. If not otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art. Example 1
[0049] The preparation method of the multi-layer carbon-coated silicon-carbon composite material of this embodiment comprises the following steps:
[0050] 200g xylose and 150g sucrose were dissolved in 2000mL pure water, and 400g silicon powder with an average particle size of 50nm and 5g hexadecyltrimethylammonium bromide were added in turn. The mixture was stirred at 25℃ and 1000rpm for 30min for preliminary mechanical dispersion, and then heated to 70℃ and stirred at 350rpm for 24h until the slurry became viscous. The uniformly dispersed slurry was dried in an oven at 100℃ for 12h to obtain a silicon-carbon precursor. Under the protection of argon atmosphere, the silicon-carbon precursor was placed in a tube furnace and heated at a heating rate of 1℃ / min, and kept at 300℃ for 30min, and then continued to heat to 750℃ and kept for 1h for the first high-temperature carbonization. After cooling to room temperature, the material was placed in a high-energy ball mill for ball milling. The ball milling setting parameters were: speed 420r / min, 200g 20mm zirconium ball, 400g 12mm zirconium ball, and ball milling time 30min. The ball-milled sample was passed through a 625-mesh molecular sieve to obtain a Si@C composite material with a particle size of about 20 μm.
[0051] 350g of asphalt was melted and softened in a muffle furnace at 400℃, and then 400g of Si@C composite material was gradually and slowly added, and stirred at 300rpm for 1h at 400℃ until the two were evenly mixed. The molten material was added to an extrusion wire drawing machine, and wired through a small hole of 200~300μm at a heating temperature of 400℃ and a pressure of 2 tons, and then entered a cooling device after a vertical height of 1m to obtain a fibrous silicon-carbon precursor with a diameter of 50nm~2μm. Under the protection of argon atmosphere, the above materials were placed in a tubular furnace and heated at a heating rate of 1℃ / min, and kept at 300℃ for 30min, and then continued to heat to 750℃ and kept for 1h for the second high-temperature carbonization. After cooling to room temperature, the material was placed in a high-energy ball mill for ball milling. The ball milling setting parameters were: speed 420r / min, 200g of 20mm zirconium balls, 400g of 12mm zirconium balls, and time 30min. The ball-milled sample was passed through a 625-mesh molecular sieve to obtain a Si@C / carbon fiber composite material with a particle size of about 20 μm.
[0052] The sieved Si@C / carbon fiber composite material was placed in a rotary furnace for chemical vapor deposition coating, wherein the coating process parameters were set as follows: heating rate of 1°C / min, reaction temperature of 850°C, reaction time of 2h, gases used were argon, methane and acetylene, gas flow rates were 500, 50, 350sccm respectively, reaction pressure was 500Pa, and a multilayer carbon-coated composite material was obtained. Example 2
[0053] The difference between Example 2 and Example 1 is that Example 2 uses 350g of polyacrylonitrile to replace the asphalt in Example 1, and the rest is the same as Example 1. Example 3
[0054] Embodiment 3 The preparation method of the multi-layer carbon-coated silicon-carbon composite material comprises the following steps:
[0055] (1) Step (1) is the same as in Example 1;
[0056] (2) 350 g of polyacrylonitrile and 400 g of Si@C composite material were dispersed and mixed in a three-dimensional mixer for 6 h. The uniformly mixed powder was added to a cyclone wire drawing device and wire drawn at 400 ° C and 8000 rpm to obtain a fibrous silicon-carbon precursor with a diameter of 50 nm to 2 μm. The subsequent carbonization and CVD coating process were the same as in Example 1. Example 4
[0057] The difference between Example 4 and Example 1 is that Example 4 uses 2g of sodium polyacrylate to replace 5g of hexadecyltrimethylammonium bromide in Example 1, and the rest is the same as Example 1. Example 5
[0058] The difference between Example 5 and Example 1 is that Example 5 uses 300 g of xylose to replace 200 g of xylose in Example 1, and the rest is the same as Example 1. Example 6
[0059] The difference between Example 6 and Example 1 is that Example 6 uses 200g of asphalt to replace 350g of asphalt in Example 1, and the rest is the same as Example 1. Example 7
[0060] The difference between Example 7 and Example 1 is that the coating process parameters of step (3) of Example 7 are set as follows: the heating rate is 2°C / min, the reaction temperature is 900°C, the reaction time is 1h, the gases used are argon, methane and acetylene, the gas flow rates are 550, 60 and 300sccm respectively, and the reaction gas pressure is 550Pa, thereby obtaining a multi-layer carbon-coated composite material. Example 8
[0061] The difference between Example 8 and Example 1 is that Example 8 uses 350g of xylose to replace 200g of xylose and 150g of sucrose in Example 1, and the rest is the same as Example 1. Example 9
[0062] The difference between Example 9 and Example 1 is that Example 9 uses 350g of sucrose to replace 200g of xylose and 150g of sucrose in Example 1, and the rest is the same as Example 1. Example 10
[0063] The difference between Example 10 and Example 1 is that Example 10 uses 350g of glucose to replace 200g of xylose and 150g of sucrose in Example 1, and the rest is the same as Example 1. Embodiment 11
[0064] The difference between Example 11 and Example 1 is that Example 11 uses 350g of citric acid to replace 200g of xylose and 150g of sucrose in Example 1, and the rest is the same as Example 1. Comparative Example 1
[0065] Comparative Example 1 The preparation method of the multi-layer carbon-coated silicon-carbon composite material comprises the following steps:
[0066] (1) 350 g of asphalt was melted and softened in a muffle furnace at 400°C, and then 400 g of silicon powder with an average particle size of 50 nm was gradually and slowly added, and stirred at 400°C at 300 rpm for 1 hour until the two were evenly mixed. The subsequent wire drawing, carbonization and CVD coating processes were the same as in Example 1. Comparative Example 2
[0067] Comparative Example 2 The preparation method of the multi-layer carbon-coated silicon-carbon composite material comprises the following steps:
[0068] (1) Step (1) is the same as in Example 1;
[0069] (2) 350 g of asphalt was melted and softened in a muffle furnace at 400°C, and then 400 g of Si@C composite material was gradually and slowly added, and stirred at 300 rpm for 1 h at 400°C until the two were evenly mixed. Then, the roll pressing process was performed three times at a speed of 1 m / s and a roller gap of 2 mm. After the flaky material was cooled, it was crushed by a jaw crusher. The subsequent carbonization and CVD coating process were the same as in Example 1. Comparative Example 3
[0070] The difference between Comparative Example 3 and Example 1 is that the CVD coating process in step (3) is not performed in Comparative Example 3, and the rest is the same as Example 1.
[0071] The multilayer carbon-coated silicon-carbon composite material, Super P, single-walled carbon nanotube (SWCNT), polyacrylic acid (PAA) and SBR prepared in Examples 1-10 and Comparative Examples 1-3 were added to deionized water at a ratio of 94.55:1:0.15:1.3:3, stirred and mixed to form a uniform slurry, coated on copper foil, dried in a vacuum drying oven at 110°C for 12 hours, and then cut into negative electrode sheets with a diameter of 14 mm. After assembling into button cells using a metal lithium sheet as a counter electrode, PE as a diaphragm, and a 1M LiPF6 solution dissolved in a volume ratio of 1:1:1 ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) as an electrolyte, conventional electrochemical performance tests and four-probe powder resistance tests were performed, and the results are shown in Table 1.
[0072] Figure 1 Schematic diagram of the structure of the multi-layer carbon-coated composite material provided by the present invention: a carbon coating layer is formed on the surface of nano-silicon particles to constitute a Si@C composite material; the Si@C composite material is uniformly distributed in a network structure formed by carbon fibers prepared from asphalt to constitute a Si@C / carbon fiber composite material; the surface of the Si@C / carbon fiber composite material is further coated with a layer of carbon to form a final multi-layer carbon-coated composite material.
[0073] Figure 2 The SEM image of the multi-layer carbon-coated composite material prepared in Example 1 shows that the carbon-coated silicon particles in the composite material are evenly distributed in the carbon fibers of the 3D porous network structure, and a thin and uniform amorphous carbon layer is coated on the surface. The multi-layer carbon-coated composite material obtained in Example 1 was tested by X-ray diffraction technology ( Figure 3), indicating that there are mainly diffraction peaks of crystalline silicon and amorphous carbon. The silicon content measured by energy dispersive X-ray spectrometer accounts for 56.13% of the total mass of the composite material, which is close to the theoretical designed Si / C mass ratio (1:1).
[0074] Table 1 Test results of Examples 1 to 10 and Comparative Examples 1 to 3
[0075]
[0076] According to the data in the table and the results in the attached figure, the multi-layer carbon-coated composite material of the present invention has good electrochemical performance as a negative electrode material for lithium-ion batteries, and the initial coulombic efficiency and the capacity retention rate after 100 cycles are both above 80%, and it has good conductivity. In particular, the composite material prepared in Example 1 has the best performance as a negative electrode material, such as Figures 4 and 5 As shown in the figure, at a current density of 0.1C, the first charge and discharge specific capacities of the multilayer carbon-coated composite material are 1632.8 mAh / g and 1848.6 mAh / g, respectively, with a first efficiency of up to 88.3%. In addition, the capacity retention rate is 94.59% after 100 cycles at a high current density of 1C. At the same time, the composite material has the lowest resistance value, with a powder resistivity of 0.136Ω·cm under a pressure of 4kN and 0.052Ω·cm under 20kN. In Example 2, a different second carbon source was used, and the electrochemical performance of the prepared composite material was slightly worse, which may be due to the lower residual carbon rate of PAN fiber than that of asphalt.
[0077] By comparing Examples 1, 8-11, it can be seen that when the first carbon source is xylose, sucrose and glucose, the electrochemical performance of the prepared composite material is worse than that when the first carbon source is a mixture of xylose and sucrose; when the first carbon source is citric acid, its electrochemical performance as a negative electrode material is even worse.
[0078] In Comparative Example 1, the nano silicon powder loses its internal hard carbon coating, and the nano silicon powder is directly added to the carbon source for drawing, which leads to uneven material mixing and a large amount of silicon powder agglomeration, thereby affecting the particle size and drawing quality. Although it has a relatively high battery capacity, its initial efficiency and cycle stability are poor. In Comparative Example 2, there is no carbon fiber conductive network structure, which is only a three-layer carbon-coated composite material, lacking a buffer for the volume expansion of silicon, further reducing its cycle stability, conductivity and reversible capacity. The lack of the outermost amorphous carbon layer in Comparative Example 3 may cause the particles attached to the surface of the carbon fiber to fall off, which is not conducive to the stable formation of the SEI film, giving it the worst cycle life.
[0079] The various aspects, embodiments, and features of the present invention should be considered to be illustrative in all aspects and not limiting of the present invention, the scope of which is defined solely by the claims. Other embodiments, modifications, and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.
[0080] In the preparation method of the present invention, the order of each step is not limited to the order listed. For those skilled in the art, without creative work, the order of each step is also within the protection scope of the present invention. In addition, two or more steps or actions can be performed simultaneously.
[0081] Finally, it should be noted that the specific embodiments described herein are merely examples of the present invention, and are not intended to limit the implementation methods of the present invention. A person skilled in the art of the present invention may make various modifications or supplements to the specific embodiments described, or replace them in a similar manner. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.
Claims
1. A method for preparing a multi-layer carbon-coated silicon-carbon composite material, characterized in that: The following steps are involved: S1, adding nano silicon powder and surfactant to an aqueous solution containing a first carbon source, stirring evenly, and drying to obtain a silicon-carbon precursor; In an inert atmosphere, the silicon-carbon precursor is subjected to a first high-temperature carbonization, ball-milled, and sieved to obtain a Si@C composite material; S2, adding Si@C composite material to the softened second carbon source, stirring evenly, and drawing to obtain a fibrous silicon-carbon precursor; subjecting the fibrous silicon-carbon precursor to a second high-temperature carbonization under an inert atmosphere, ball milling, and sieving to obtain a Si@C / carbon fiber composite material; S3, chemical vapor deposition of the Si@C / carbon fiber composite material under an inert atmosphere and a third carbon source atmosphere to obtain a multi-layer carbon-coated silicon-carbon composite material; The first carbon source is a mixture of xylose and sucrose in a mass ratio of 1 to 2:1; The mass ratio of the nano silicon powder to the first carbon source is 0.5-5:1; In step S2, the mass ratio of the second carbon source to the Si@C composite material is 0.1-2:1; The conditions of the first high-temperature carbonization and the second high-temperature carbonization include: a heating rate of 0.5-10°C / min, a carbonization temperature of 700-1000°C, and a carbonization time of 0.5-5h; The second carbon source is asphalt or polyacrylonitrile; During the wire drawing process of step S2, the heating temperature is 300-400°C, and the diameter of the fibrous silicon-carbon precursor obtained by wire drawing is 10nm-2μm.
2. The preparation method according to claim 1, characterized in that: The average particle size of the nano silicon powder is 1-100 nm.
3. The preparation method according to claim 1, characterized in that: The surfactant is one or more of hexadecyltrimethylammonium bromide, dodecyltrimethylammonium bromide, polyvinylpyrrolidone, sodium carboxymethylcellulose, and sodium polyacrylate.
4. The preparation method according to claim 1, characterized in that: In the aqueous solution containing the first carbon source, the concentration of the first carbon source is 10-800 g / L; After adding the surfactant, the concentration of the surfactant is 0.1~100g / L.
5. The preparation method according to claim 1, characterized in that: The conditions for ball milling in steps S1 and S2 include: a ball milling speed of 150-500 r / min, and a ball milling time of 0.5-2 h; The sieving mesh numbers in steps S1 and S2 are 100 to 800 meshes respectively.
6. The preparation method according to claim 1, characterized in that: The second carbon source is heated and softened at a high temperature in a muffle furnace, wherein the softening temperature is 380-500°C; The stirring time of step S2 is 0.5-3 h, and the stirring speed is 100-800 rpm.
7. The preparation method according to claim 1, characterized in that: In step S3, the third carbon source is one or more of acetylene, methane, ethanol, and ethylene; The gas flow rate of the third carbon source atmosphere is 50-600 sccm, the gas flow rate of the inert atmosphere is 400-800 sccm, and the reaction gas pressure is 300-700 Pa.
8. The preparation method according to claim 1, characterized in that: The conditions for chemical vapor deposition in step S3 include: a heating rate of 1-10° C. / min, a temperature of 800-1000° C., and a time of 0.5-5 h.
9. A multi-layer carbon-coated silicon-carbon composite material prepared by the preparation method as claimed in claim 1.
10. Use of the multi-layer carbon-coated silicon-carbon composite material in a lithium-ion battery according to claim 9, characterized in that: The negative electrode sheet of the lithium-ion battery comprises the multi-layer carbon-coated silicon-carbon composite material.
Citation Information
Patent Citations
Preparation method of silicon-carbon composite lithium ion battery negative plate
CN104577053A
Method for preparing surface-modified SiOx electrode material
CN109728281A
Silicon-carbon composite material, and preparation method and application thereof
CN112652742A